2001
DOI: 10.1080/14756360109162387
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Succinate-cytochrome C Reductase by a Ferromacrocyclic Complex

Abstract: Succinate-cytochrome c reductase (SCR) from mouse liver was inhibited strongly and reversibly by an iron (II) macrocyclic complex 3. The inhibition was observed for the enzyme toward the reduction of both 2,6-dichlorophenol indophenol (DCIP) and cytochrome c (cyt c). The inhibition was a mixed type and noncompetitive with respect to the reduction of DCIP and cyt c, respectively. Values of the inhibition constant ranged from 6.6 to 8.3 microM. The IC50 for the complex 3 was found to be 16.6 +/- 0.8 and 12.1 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Detection of the reversibility of binding of compounds 2 and 3 to ATCase. The reversibility of binding of each compound to ATCase was studied as described before for other enzymes [38,39]. Briefly, 1.0 mL of 0.2 mM of each compound was added to 1.0 mL of the enzyme for 60 min at room temperature and the mixture was then put in a cellophane bag.…”
Section: Enzyme Assaymentioning
confidence: 99%
“…Detection of the reversibility of binding of compounds 2 and 3 to ATCase. The reversibility of binding of each compound to ATCase was studied as described before for other enzymes [38,39]. Briefly, 1.0 mL of 0.2 mM of each compound was added to 1.0 mL of the enzyme for 60 min at room temperature and the mixture was then put in a cellophane bag.…”
Section: Enzyme Assaymentioning
confidence: 99%
“…It is associated with various degrees of hepatic dysfunction and severe cases of infection can be fatal [10,12]. It has been reported that changes in some enzymes occur during S. mansoni infection and these enzymes belong to different classes of classification [1,2,14,17].…”
Section: Introductionmentioning
confidence: 99%